A Multiplicity of Voices in Grace Nichols’s Work - Mišterová, Ivona (American & British Studies Annual, 2018)
Review of Pavlína Flajšarová, Grace Nichols Universal and Diverse: Ethnicity in the Poetry of Grace Nichols. Olomouc: Palacky University in Olomouc, 2016. 318 p. ISBN 978–80–244–4970–8